Estudo, levantamento e dimensionamento de um sistema solar fotovoltaico de geração de energia utilizando os softwares HOMER e PV size na ilha Nazaré, rio Maracapucú, Abaetetuba-PA - RODRIGUES, Marinaldo de Jesus dos Santos (2022)
The use of photovoltaic energy is a potential alternative for the generation of electricity. In rural areas can use this technology to reduce the suffering of residents caused by the lack of electricity. Since the applications of solar photovoltaic are quite diverse and can be used as a source in isolated or connected to the network systems. This paper conducted a survey of a village in Nazareth Island, rural Abaetetuba - PA in order to know the installed load, load and consumption of generator fuel profile of the village and from these data sizing a PV system autonomous. To obtain the data of radiation used the Radiasol 2 software, based on the city of Belém - PA. We carried out the calculations for sizing the system and after this step two simulations were conducted in two software in order to lend credibility to the study. The program used were Homer and PVSize. We compared the data obtained by the two software’s with the intention of checking whether values were correlated. To complete an analysis of comparative cost between the generation of energy from photovoltaic panels and the generation of the village generator is presented.